Openness to Experience as a Moderator of the Relationship between Intelligence and Creative Thinking: A Study of Chinese Children in Urban and Rural Areas - Shi, Baoguo; Dai, David Y.; Lu, Yongli (Frontiers in Psychology, 2016)
Using testing and questionnaire methods, this study investigated the relationships among openness to experience, intelligence and creative thinking. This study focused on the moderating effects of openness to experience on the relationship between intelligence and creative thinking in a sample of 831 primary school students in China. The findings showed significant positive relationships among openness to experience, intelligence and creative thinking. In relation to the focus of this study, openness to experience moderated the relationship between intelligence and creative thinking. However, the correlation between openness to experience and creative thinking was stronger for urban children than for rural children, and the moderating effect existed only in urban settings.